Analisis Faktor-Faktor Yang Mempengaruhi Kepemimpinan Pendidikan Islam - Masruri; Sarnubi; Linda; Almahfuz (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
Leadership in Islamic education plays a crucial role in determining the direction and quality of educational institutions. This study aims to analyze the factors influencing Islamic educational leadership by employing a library research method. Data were collected from relevant literature, including books, journal articles, proceedings, and academic documents, and analyzed using a descriptive-analytical approach. The findings reveal that leadership effectiveness is shaped by two main groups of factors: internal and external. Internal factors consist of abilities, personal qualities, and leadership styles, where democratic–transformational leadership proves to be more effective in fostering participation, improving learning quality, and strengthening public trust. External factors include social, economic, cultural, political, and geographical aspects that form the broader context of leadership and require leaders to be adaptive to change. The synthesis of Islamic values and modern leadership theories produces a conceptual model of ideal Islamic educational leadership that is grounded in prophetic values, responsive to socio-cultural contexts, and adaptive to contemporary developments. This study is expected to enrich the academic literature and provide practical contributions for leaders of Islamic educational institutions in enhancing educational quality and human resource development.